Effects of Biochar Application on Winter Wheat (Triticum aestivum L.) Roots Under Long-Term Drought Conditions - Svoboda, Zdeněk; Záhora, Jaroslav; Dvořáčková, Helena (Mendelova univerzita v Brně, 2017)
The main objective of this paper was to evaluate the effect of applying biochar and activated carbon on winter wheat affected by drought in model laboratory conditions. Cultivation tests of the soil-microorganisms-plant (winter wheat) system were focused on understanding the interactions between microbial soil communities and experimental plants in response to specific cultivation measures, in combination with the modelled effect of drought. The containers were formed as a split-root rhizotron. In this container experiment, the root system of one and the same plant was divided into two separate compartments where into one half, biochar or activated carbon has been added. The other half without additives was a control. Plants favoured the formation of the root system in the treated part of the container under both drought and irrigation modes. In drought mode there was lower production of CO2, lower overall length and surface of the roots of winter wheat compared to variants in irrigation mode. The application of biochar and activated carbon, therefore, supported the colonization of roots by mycorrhiza in general. The Scientific merit of this paper was to investigate the possibility of mitigating the effects of a long-term drought on winter wheat through the application of biochar or the application of activated carbon.
Keywords: soil; mycorrhiza; split-root rhizotron; biochar; CO2; N2O; roots